Smaller Absolute Quantities but Greater Relative Densities of Microvessels Are Associated with Cerebellar Degeneration in Lurcher Mice - Kolinko, Yaroslav; Cendelin, Jan; Kralickova, Milena; Tonar, Zbynek (Frontiers in Neuroanatomy, 2016)
Degenerative affections of nerve tissues are often accompanied by changes of vascularization. In this regard, not much is known about hereditary cerebellar degeneration. In this study, we compared the vascularity of the individual cerebellar components and the mesencephalon of 3-month-old wild type mice (n = 5) and Lurcher mutant mice, which represent a model of hereditary olivocerebellar degeneration (n = 5). Paraformaldehyde-fixed brains were processed into 18-μm thick serial sections with random orientation. Microvessels were visualized using polyclonal rabbit anti-laminin antibodies. Then, the stacks comprised of three 5-μm thick optical sections were recorded using systematic uniform random sampling. Stereological assessment was conducted based on photo-documentation. We found that each of the cerebellar components has its own features of vascularity. The greatest number and length of vessels were found in the granular layer; the number of vessels was lower in the molecular layer, and the lowest number of vessels was observed in the cerebellar nuclei corresponding with their low volume. Nevertheless, the nuclei had the greatest density of blood vessels. The reduction of cerebellum volume in the Lurcher mice was accompanied by a reduction in vascularization in the individual cerebellar components, mainly in the cortex. Moreover, despite the lower density of microvessels in the Lurcher mice compared with the wild type mice, the relative density of microvessels in the cerebellar cortex and nuclei was greater in Lurcher mice. The complete primary morphometric data, in the form of continuous variables, is included as a supplement. Mapping of the cerebellar and midbrain microvessels has explanatory potential for studies using mouse models of neurodegeneration.